A Novel Metal–Organic Framework (MOF)–Mediated Interfacial Polymerization for Direct Deposition of Polyamide Layer on Ceramic Substrates for Nanofiltration. Issue 9 (2nd April 2019) - Bao, Yueping; Chen, Yunfeng; Lim, Teik‐Thye; Wang, Rong; Hu, Xiao
Abstract: A facile metal–organic framework (MOF)‐mediated interfacial polymerization (IP) method is developed to prepare a polyamide (PA) layer directly on the ceramic substrate for nanofiltration. MOF is introduced to connect ceramic substrate and PA layer via chemical bonding, resulting in a robust separation layer. The optimization of IP can be controlled by MOF growth process via tuning the surface roughness as well as hydrophilicity. This method will provide a new way for the preparation of next generation of organic–inorganic composite membranes. Abstract : The work opens a new way to prepare organic–inorganic composite membrane for nanofiltration . A well‐defined metal–organic framework is utilized as the intermediate layer to facilitate the interfacial polymerization on ceramic substrate via tuning its morphology and surface chemistry. The chemical bonding between substrate and polyamide layer make the composite membrane more stable and robust.